2022
DOI: 10.1016/j.jhepr.2022.100446
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-derived hepatocyte system models cholestasis with tight junction protein 2 deficiency

Abstract: A, Human iPSC-derived hepatocyte system models cholestasis with tight junction protein 2 deficiency, JHEP Reports (2022), doi: https://doi.org/10.1016/j.jhepr.2022.100446. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 44 46 Disease studies using human iPSC-derived hepatocytes and inducible knockout mice support the contribution of Tjp2 to hepatobiliary development during the fetal and neonatal periods. 45 , 47 In addition to TJP2 , several other Ped-CLD-causing genes have been identified that may play a role during the fetal and neonatal period, including MYO5B, LSR, ZFYVE19 , and KIF12 . 2 , 36 , 48 By delivering AAV8 sgRNA to the fetus, the system established in this study can be applied to evaluating these genes.…”
Section: Discussionmentioning
confidence: 99%
“… 44 46 Disease studies using human iPSC-derived hepatocytes and inducible knockout mice support the contribution of Tjp2 to hepatobiliary development during the fetal and neonatal periods. 45 , 47 In addition to TJP2 , several other Ped-CLD-causing genes have been identified that may play a role during the fetal and neonatal period, including MYO5B, LSR, ZFYVE19 , and KIF12 . 2 , 36 , 48 By delivering AAV8 sgRNA to the fetus, the system established in this study can be applied to evaluating these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Culturing Human iPSCs and CRISPR/Cas9 editing of GBE1: Human specimens were obtained from patients according to ethically approved protocols (Study ID: 2014–6705 for the Institutional Review Board of Cincinnati Children's Hospital Medical Center). Human iPSCs were edited by CRISP/Cas9 in a method described previously [ 20 ]. Briefly, control iPSCs (clone code: 1383D6), characterized for pluripotency, karyotyped, and provided by Kyoto University [ 21 ], underwent CRISPR/CAS9 genome-editing to introduce homozygous GBE1 VUS (c.2081T>A (p.Ile694Asn) by selecting candidate single-guide RNA (sgRNA) from CRISPOR ( http://crispor.org/ ), with exceptionally high scores for specificity [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis and GBE1 enzyme activity measurement: Western blot analysis of GBE1 protein was performed using a method previously published [ 20 ]. Briefly, proteins were isolated using Cell Lysis Buffer (Cell Signaling Technology # 9803) with a proteinase and phosphatase inhibitor cocktail.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas ASCs are isolated directly from the tissue of interest, hiPSCs are obtained in a non-invasive manner from different adult tissue cell sources such as erythroblasts isolated from the PBMC fraction of blood or from urine-derived epithelial cells. Consequently, the increased utility and availability of hiPSCs have directed research toward the development of numerous protocols that outline culturing methods to obtain hepatocyte-like cells (HLCs) for drug metabolism studies ( Mallanna & Duncan, 2013 ; Mun et al, 2019 ; Pettinato et al, 2019 ; Thompson & Takebe, 2020 ; Kim et al, 2022 ; Li et al, 2022 ; Messina et al, 2022 ; Pettinato, 2022 ; Weng et al, 2023 ; Zhang et al, 2023 ). However, it should be noted that although 2D cultured hiPSCs have advantages compared to cancer cell lines and primary hepatocytes in terms of isolation and culturing, they still do not fully represent the structural and physiological complexity of the human liver.…”
Section: In Vitro 2d Model Systemsmentioning
confidence: 99%